Online-dominant self-management is associated with lower, while hybrid mode is associated with higher, quality of life: a community-based cross-sectional study - Xuanyu Wang; Fan He; Qinli Zhang; Yang Meng; Ting Chen; Ye Zhu (Frontiers in Public Health, 2026)
Background Health-related quality of life (HRQoL) is an important outcome measure for evaluating community health interventions. Exploring effective community-based health self-management strategies is of practical significance in the context of population aging. This study compared the associations of different activity delivery modes (hybrid online-offline, offline-dominant, and online-dominant) implemented within community health self-management groups on residents’ HRQoL, and explored associations with activity-related factors and demographic factors. Methods A cross-sectional survey was conducted among 1,697 residents in Baoshan District, Shanghai. The 36-Item Short Form Health Survey (SF-36) was used to assess Physical Component Summary (PCS) and Mental Component Summary (MCS) scores. Multiple linear regression was employed to adjust for demographic covariates, and estimated marginal means were used to estimate between-group mean differences (MD) with 95% confidence intervals (CI). Results After adjusting for demographic factors, the hybrid online-offline group had significantly higher PCS (MD = 3.96, 95% CI: 1.65 to 6.26) and MCS (MD = 5.44, 95% CI: 3.10 to 7.79) compared with general residents (both p < 0.001). In contrast, the online-dominant group had significantly lower PCS (MD = −6.84, 95% CI: −10.01 to −3.67, p < 0.001) and MCS (MD = −5.72, 95% CI: −8.98 to −2.46, p < 0.01). The offline-dominant group showed no significant differences from general residents. The exercise-only group had significantly higher MCS than general residents (MD = 5.60, 95% CI: 1.18 to 10.04, p < 0.05). Activity frequency of no more than once per week was associated with higher PCS (MD = 3.20, 95% CI: 0.96 to 5.45, p < 0.01) and MCS (MD = 3.14, 95% CI: 0.86 to 5.43, p < 0.01), whereas frequency exceeding twice per week was associated with lower MCS (MD = −4.11, 95% CI: −7.19 to −1.04, p < 0.01). Female sex, older age, and poorer economic status were associated with lower PCS. Conclusion In this community-based cross-sectional study, the hybrid online-offline mode was associated with better HRQoL, while the online-dominant mode was associated with poorer HRQoL. Exercise activities were associated with better mental health; however, higher frequency was not necessarily associated with better outcomes. Participation at a frequency of no more than once per week was associated with higher HRQoL scores. Given the cross-sectional design, these findings should be interpreted as associative and hypothesis-generating rather than causal, and prospective studies are needed to confirm the observed associations.